Room Temperature Phosphorescence of Chlorine Doped Carbon Nitride Dots - Patir, Khemnath; Gogoi, Sonit Kumar (Frontiers in Chemistry, 2022)
Metal free room temperature phosphorescent materials have stimulated considerable attention due their potential applications in optoelectronic devices, sensing and security and safety signage. An efficient fluorescent and phosphorescent chlorine doped carbon nitride dots (Cl-CNDs) have been prepared by thermal treatment of guanidine hydrochloride. The Cl-CNDs prepared is characterized by FESEM, DLS,PXRD, EDX, TGA, FT-IR and UV-Visible spectroscopy. The Cl-CNDs exhibit a long phosphorescence lifetime of 657 ms and its phosphorescence quantum yield is found to be 2.32 % upon excited at 360 nm in air. The formation of compact cores particles via condensation along with hydrogen bonding of Cl-CNDs by its functional groups facilitate intersystem crossing and stabilizes the triplet states, favouring room temperature phosphorescence. The cost effective preparation and tunable optical properties of Cl-CNDs may offer its applications in security encryption and optoelectronic devices.